Lon Po Po : a Red-Riding Hood story from China - Young, Ed.; Juvenile Collection (Library of Congress) (New York Scholastic, 1990)
Three sisters staying home alone are endangered by a hungry wolf who is disguised as their grandmother.
M
b
b
Keywords: Folklore